The Social Sciences in Hungary During the Cold War and After - Karády, Viktor (Serendipities. Journal for the Sociology and History of the Social Sciences, 2021)
Based on various types of recently explored empirical evidence, this study attempts to account for the complex and ever-changing relationship the social sciences in Hungary have entertained with their foreign counterparts, both institutionally and through their intellectual references since their birth in the early 20th century. Historically, up until Communist times, Hungary was a German intellectual colony of sorts while remaining receptive mostly to French and other influences as well. This changed fundamentally after 1948 with the process of Sovietization. This implied the outright institutional suppression of several social disciplines (sociology, demography, political science, and psychoanalysis) and the forceful intellectual realignment of others along Marxist lines. Contacts with the West were also suspended and the exclusive orientation to Soviet social science enforced throughout the long 1950s. A thaw period after this attempt at Russian cultural colonization followed the years after the 1956 anti-Bolshevik uprising. From 1963 on, the Hungarian social sciences saw the reestablishment and state-supported promotion of disciplines that were suppressed earlier, the softening of the ascendancy of official Marxism, and the opening of channels of exchange with the West. In spite of the continuation of political censorship, ideological surveillance, and occasional expulsion of politically dissident scholars until 1989, Hungarian social scientists could benefit more often and intensively from Western sponsorship (such as study grants from the Ford foundation) and collaborations. After the fall of Communism, the expansion and reorientation of the social sciences to the West, dominated by Anglo-Saxon contacts, are demonstrated by various indices, such as data on the book market of the social sciences and books purchased by libraries, translated, or cited in major reviews.